A MoS2–based system for efficient immobilization of hemoglobin and biosensing applications. (18th June 2015) - Chao, Jie; Zou, Min; Zhang, Chi; Sun, Haofan; Pan, Dun; Pei, Hao; Su, Shao; Yuwen, Lihui; Fan, Chunhai; Wang, Lianhui
Abstract: A novel hydrogen peroxide (H2 O2 ) and nitric oxide (NO) biosensor was fabricated by immobilizing hemoglobin (Hb) on a gold nanoparticle-decorated MoS2 nanosheet (AuNPs@MoS2 ) nanocomposite film modified glass carbon electrode. The AuNPs@MoS2 nanocomposite not only made the immobilized Hb keep its native biological activity but also facilitated the electron transfer between electrode and the electroactive center of Hb due to its excellent conductivity and biocompatibility. The direct electrochemistry and bioelectrocatalytic activity of Hb were investigated by cyclic voltammetry (CV). The modified electrode showed good electrocatalytic ability toward the reduction of H2 O2 and NO. Under optimal conditions, the current response was linear with the concentration of H2 O2 and NO in the range from 10 to 300 μ M and 10 to 1100 μ M with a detection limit of 4 and 5 μ M, respectively. This MoS2 -based biosensor was sensitive, reproducible and stable, indicating that AuNPs@MoS2 nanocomposite maybe a promising platform to construct electrochemical sensors for chemical and biological molecules detection.